Mechanical and energy absorption properties of 3D-printed honeycomb structures with Voronoi tessellations - Ahmed, Abdelrahman Mohamed Ragab M.; Mahdi, Elsadig; Oosterhuis, Kas; Dean, Aamir; Cabibihan, John-John (Frontiers in Mechanical Engineering, 2023)
3D printing technology is the new frontier in building construction. It is especially useful for making small structures within a short period. Full construction, including interior partitions and exterior façades, can be achieved with this technology. This paper proposes a parametric Voronoi tessellations model for quickly generating and fabricating 3D-printed hexagonal honeycomb partitions for interior design. Comprehensive experimental testing was conducted to characterize the mechanical properties and investigate the energy absorption characteristics of the proposed 3D-printed hexagonal honeycomb while comparing it to alternative hexagonal honeycomb structures. The tests included tensile testing (ASTM-D638) of the printed Polylactic Acid (PLA) material, especially with the almost total absence of conducted research that reported mechanical properties for 3D printed material with low infill percentages such as 10%. In addition, an in-plane quasi-static axial compression testing of the lightweight honeycomb structures was also conducted on the printed structure with the same low infill percentage. Compared to non-Voronoi honeycomb structures, the Voronoi honeycomb resulted in superior mechanical and energy absorption properties with energy absorption values ranging from 350 J to 435 J and crash force efficiency being 1.42 to 1.65.